Factors Influencing the Population Fluctuations of Euproctis chrysorrhoea (Lepidoptera: Erebidae) in Maine. Issue 5 (27th June 2021) - Boyd, Karla S; Drummond, Francis; Donahue, Charlene; Groden, Eleanor
Abstract: The browntail moth ( Euproctis chrysorrhoea (L.)) is a forest pest that was accidentally introduced in the late 1800's and spread throughout New England in the early part of the 20th Century. At its peak range expansion in 1915 it encompassed an area of 150, 000 km 2 after which populations declined. By the 1960s, its distribution had receded to relic populations on outer Cape Cod, MA, and islands in Casco Bay, ME. In 1989 browntail moth resurged in Maine, with periodic, moderate outbreaks before a dramatic increase of the population occurred in 2016. We examined the pattern of annual defoliation by browntail moth since its resurgence in the 1990s as well as variation in populations throughout infested areas in Maine during three years of the recent outbreak, 2016–2018, relative to differences in weather, parasitism and habitat characteristics. Levels of defoliation over 24 yr were predicted by the preceding spring precipitation (−, negative effect) and the year's previous late summer and early fall temperatures (+, positive effect) when first to third instar larvae feed and then construct winter hibernacula. Late summer temperatures predicted the abundance of hibernacula across outbreak areas (+). Early spring temperatures (+) and early and late spring precipitation (−) predicted early summer larval and pupal nest abundance. Warmer fall temperatures result in more mature populations coming out of winter hibernacula in the spring, whereas spring precipitation drives epizootic outbreaks of Entomophaga aulicae (Reichardt in Bail) Humber (Entomophthorales: Entomophthoraceae). with parasitoids playing a lesser role. Climate trends indicate continued increases in fall temperatures since browntail moth resurgence.